PENGARUH KONFLIK KERJA, STRESS KERJA DAN KEPUASAN TERHADAP KINERJA Karyawan ( Studi Pada Perusahaan Daerah Air Minum Kabupaten Demak ) - Anita Zusrotun Nafiah, 14.05.51.0181; Rijanti, TRistiana (Students' Journal of Economic and Management, 2018)
This research to analyzed the effect of work conflict, work stress, and job satisfaction on performation. The sample technical used random sampling with 113 responden. Data analysed by multiple regression linier by spss. .The results of the study showed that simultaneously variable independent together influential dependent on variables. Parsial variable work conflict has not been affecting the employee performance, work stress have a positively effect significantly effect on of employee performance, job satisfaction have a positively effect significantly effect on employee performance. Password: work conflict, work stress, job satisfaction and employee performance .